Asosiasi Echinodermata pada Ekosistem Padang Lamun di Pantai Samuh, Nusa Dua, Bali - Vindia, Wahyu Ilvita; Julyantoro, Pande Gde Sasmita; Wulandari, Endang (Journal of Marine and Aquatic Sciences; Vol 5 No 1 (2019)DO - 10.24843/jmas.2019.v05.i01.p13, 2018)
Seagrass beds and their associate biota are very important in maintaining the balance of coastal ecosystems. Samuh Beach is one of seagrass ecosystem area in Bali Island. One of the biota that exists in the seagrass ecosystem in Samuh Beach is Echinodermata. Since the limited information and the complex activities at Samuh Beach make research about associations of Echinodermata with seagrass, this research seems become important to be conducted. This study was aimed to determine the density of species, species composition, and distribution patterns of lamun and Echinodermata in the coastal waters of Samuh beach. Data analysis was performed by using density type, species composition, dispersion index of morisita and association. The average seagrass density of each station in Samuh coastal waters ranged from 156-246 stands/m2 and the highest density of Echinoderms is Diadema setosum in each station. The species composition of seagrass in Samuh beach comprises five species of seagrass namely: Enhalus acoroides, Halophila ovalis, Thalassodendron ciliatum, Cymodocea serrulata and Syringodium isoetifolium. The composition of Echinodermata species that found amounted to 13 species of Echinodermata namely: Diadema setosum, Amphiura sp., Archaster typicus, Asterias sp., Mespilia globulus, Tripneustes gratilla, Pseudoboletia maculata, Protoreaster nodusus, Ophiactis resillens, Ophiopteris antipodum, Centrostephanus rodgersii, Echinothrix and Echinothrix mathei. Based on the calculation of morisita, seagrass and Echinodermata Index in Samuh Beach was spread uniformly and clumped. The result of association analysis showed that there were positive association, negative association and association with no relation between seagrass and Echinodermata in Samuh Beach.